Line manager involvement in HRM - Renwick, Douglas (Employee relations, 2003)
For many years, there has been immense speculation about the advisability of devolving human resource management (HRM) issues to line managers(Hall and Torrington, 1998; Ulrich, 1998; Gratton et al., 1999). On the one hand it is argued that HR resides properly with the people directly responsible for supervising staff whose primary purpose is to manufacture products, sell goods and equipment or provide a public or customer service. While there might be problems ensuring that these line managers have sufficient knowledge and skills to supervise staff effectively and consistently, it is nevertheless maintained that these individuals are in the best position to adopt the most appropriate human resource (HR) styles and practices (Cunningham and Hyman, 1999; Sisson and Storey, 2000; Cooper, 2001). On the other hand, there are claims that effective HRM cannot be delivered by line managers whose primary responsibilities lie elsewhere, namely in meeting service or production goals, and who have scant regard for learning how to find ways to get the best out of their staff. Under this scenario, it is argued that line managers are bound to need continuous and systematic support and training from HR specialists to ensure that they do not make mistakes that can be costly at a later date (Earnshaw et al., 2000; Renwick, 2000; Marchington and Wilkinson, 2002).